Validation of renal and hepatic profile parameters of rodents Rattus novergicus kept in the maintenance vivarium of the University of Franca (Research, Society and Development, 2020)
Due to the high use of animals as experimental models for pharmaceutical trials, especially rats, it is necessary to standardize reference values for the evaluation of liver perfil by the analytes alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and renal function, through the analytes urea and creatinine. For this purpose, samples were collected from 169 samples of Rattus norvegicus of Wistar strain, from the Vivarium of the University of Franca (SP), provided of semi-automated analytical methodology. For the calculation of the value, mean and standard deviation were performed for standardization and for the creation of reference values, therefore -2DP for minimum value determination and + 2DP for maximum value were used. The liver enzyme ALT presented a reference range from 21 to 96 U / L, while the AST from 44 to 186 U / L. In renal markers, urea was 20 to 73 mg / dL and creatinine 0.23 to 0.77 mg / dL. Given the applied methodology and the results obtained, it is admitted that it is very important to standardize the reference values of analytes in animal houses due to geographical changes, protocols, diets, among others; In addition, reducing the use of animals in experimental procedures in addition to guiding researchers on animal health and assisting analysis in various experimental research projects.